How to Build a Network that Facilitates Firm-level Innovation: An Integration of Structural and Managerial Perspectives - Fabian Reck; Alexander Fliaster; Michael Kolloch (Journal of Management Studies, 2021)
In this paper, we examine to what extent the firm's propensity to be embedded in a network with advantageous structural attributes is driven by its capabilities for network management. Specifically, we discern network management practices on two organizational levels (relationship management (RM) and portfolio management (PM)) and explore their effects on three dimensions of local network structure (network centrality (NC), knowledge complementarity (KC), and tie strength (TS)). To test our hypotheses, we collect sociometric survey data from the largest inter-firm network in the German energy industry. The results indicate that intra-firm processes for network management indeed are key enablers of structural network advantages. Further, we demonstrate that RM and PM exert distinct effects: PM helps the firm improve NC, RM leads to increased TS, and KC results from an additive effect of the two capabilities. In all, our work contributes to theory on strategic networks by providing an integrated perspective on how network structure and network management benefit innovation performance.
Keywords: 650; strategic networks; network structure; network management; organizational capabilities; innovation